Peningkatan Kemampuan Kognitif Mengklasifikasi Benda Melalui Aktivitas Bermain Dengan Media Alam Di Rumah Pada Masa Pandemi Covid 19 Pada Peserta Didik Kelompok A Tk Marsudi Ilmi Cabak Kecamatan Tlogowungu Kabupaten Pati - Dyah Kusbiantari; Wahyuni Wahyuni; Nuryanti Nuryanti (Sentra Cendekia, 2022)
This research is a study on increasing cognitive ability to classify objects through playing activities with natural media at home during the Covid 19 pandemic. The background of this research is that students' ability to classify objects is still low. It is evident from the 15 children, only 4 students or 26.67% are included in the BSB and BSH categories. The purpose of this study is to prove that the use of playing activities with natural media at home can improve cognitive ability to classify objects during the Covid 19 Pandemic Period in Group A Students of Marsudi Ilmi Cabak Kindergarten, Tlogowungu District, Pati Regency. This research belongs to the type of Classroom Action Research. The action plan consists of two cycles, namely: cycle I, and cycle II with each cycle having two meetings, with each cycle consisting of four stages, namely: planning, implementing actions, observing and reflecting. The subjects studied were 15 children in group A of Marsudi Ilmi Tlogowungu Pati Kindergarten, consisting of 7 boys and 8 girls. Data collection techniques include observation, interviews and documentation. While the data analysis techniques include: qualitative analysis and comparative analysis by calculating the percentage of children's cognitive abilities which are then compared to the percentage of completeness pre-cycle, cycle I, and cycle II. The results of the study prove that the use of playing activities with natural media at home can improve cognitive ability to classify objects during the Covid 19 pandemic in group A students of Marsudi Ilmi Cabak Kindergarten, Tlogowungu District, Pati Regency, for the 2020/2021 Academic Year. It is evident from the cognitive ability to classify students' objects in the pre-cycle which are included in the category of Very Good Developing (BSB) and Developing According to Expectations (BSH) only 26.67%. Then it increased in the first cycle of meeting 1 to 46.67% and meeting 2 to 60.00%. Then it increased again in the second cycle of meeting 1 to 63.33% and meeting 2 to 93.33%. Thus, it is known that there is an increase of 66.66%.